Eskalasi Status Gizi Balita Guna Pendayagunaan Potensi Lokal Melalui Program Pemberian Makanan Tambahan (PMT) Masyarakat Mlandingan Kulon - Prabowo, Rachmat Udhi; Kurlina, Elvira; Maulana Multazam, M.A.; Ridjal, Julian Adam; Utami, Suryanti Pristi (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The village of Mlandingan Kulon is situated near the coast, holding significant potential in the field of fisheries. Many of its inhabitants work as fishermen, and various types of fish caught by these fishermen are sold at the local market of Mlandingan Kulon Village. Among the high-quality fish catches, there is tuna. Tuna fish is a highly meaningful source of protein as it contains more than 20% protein. Protein plays a crucial role in the formation of body tissues such as muscles, bones, skin, and other organs, especially in toddlers. Nuggets have a relatively long shelf life when stored in cold or frozen conditions. Fish nuggets possess numerous advantages, including being a nutritious and valuable food, having a soft texture, a variety of flavors, and being suitable for various ages. Consequently, a campaign is being conducted to introduce the Nugget Tuna (GETTA) product to the mothers at the integrated health post of Mlandingan Kulon Village. The purpose of this campaign is to introduce processed tuna fish in the form of nuggets as Supplementary Feeding (PMT) for toddlers. These tuna fish nuggets contain beneficial nutritional content for toddler health and can help improve their nutritional status. The campaign is conducted through posters explaining the composition, benefits, and process of making tuna fish nuggets. Subsequently, a video is shown that illustrates the steps of making Nugget Tuna (GETTA). The result of this campaign is an enhancement of knowledge among the mothers at the integrated health post regarding the importance of providing Supplementary Feeding (PMT) to toddlers.